2022
DOI: 10.3390/medicina58070848
|View full text |Cite
|
Sign up to set email alerts
|

Practical Applicability of the ISARIC-4C Score on Severity and Mortality due to SARS-CoV-2 Infection in Patients with Type 2 Diabetes

Abstract: Background and objectives. There is a bidirectional relationship between SARS-CoV-2 infection and diabetes mellitus (DM), as people with DM are more vulnerable, and SARS-CoV-2 infections worsen the prognosis in these patients. The main purpose of the study was to evaluate the application validity of the ISARIC-4C score in patients confirmed with SARS-CoV-2 infection. Materials and Methods. The study included 159 patients previously known to have type 2 DM and confirmed positive for SARS-CoV-2 infection. We ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…These changes induce a prothrombotic state that causes cellular and tissue damage, especially in critical patients with multiple comorbidities. [36][37][38] In our study, patients with CVD and hypertension had a severe outcome and higher mortality rate. Patients who died had greater than 50% lung damage and SatO2 less than 80%.…”
Section: Discussionmentioning
confidence: 48%
“…These changes induce a prothrombotic state that causes cellular and tissue damage, especially in critical patients with multiple comorbidities. [36][37][38] In our study, patients with CVD and hypertension had a severe outcome and higher mortality rate. Patients who died had greater than 50% lung damage and SatO2 less than 80%.…”
Section: Discussionmentioning
confidence: 48%
“…In another study, statistical significance in mortality differences between ISARIC 4C score categories was observed during the first wave of the COVID-19 pandemic [ 32 ]. Albaie et al reported that the ISARIC 4C mortality score is useful to assess the prognosis of patients with type 2 diabetes mellitus presenting with COVID-19 with an AUC of 0.875 using a cutoff value of >14 [ 33 ]. Another study from Saudi Arabia found that the ISARIC 4C Mortality Score is an excellent tool to predict mortality in critically ill COVID-19 patients with an AUC of 0.81; the sensitivity was 70.5% and the specificity 73.97% with a cutoff value of >9 [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, proponents supported its age-agnostic approach to short-term risk stratification. Although 4C has demonstrated adequate calibration in different racial/ethnic groups ( 6 ), patients with advanced age, and those with underlying comorbidities ( 25 27 ), it relies heavily on age as the single most heavily weighted component. Here, we examined discriminative function of the m4C score by subtracting the age component and found that score AUC was diminished, but still better than that of the SOFA score reported elsewhere ( 3 , 4 ).…”
Section: Discussionmentioning
confidence: 99%